Legal Protection of Minority Shareholders in Good Corporate Governance at Bank Syariah Indonesia - Nur Rodiyah; Rudi Hermawan; Ahmad Musadad (UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the legal protection of minority shareholders at Bank Syariah Indonesia (BSI) and evaluates the implementation of Good Corporate Governance (GCG) in ensuring fair, transparent, and Sharia-compliant corporate governance. The study employs a normative-empirical legal approach by analysing Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 21 of 2008 concerning Islamic Banking, OJK regulations, GCG principles, and relevant legal literature, supported by observation and interviews at BSI Bangkalan Branch. The findings show that minority shareholder protection has been normatively recognized through several concrete rights, including the right to obtain corporate information, attend and vote in the General Meeting of Shareholders, file objections, initiate legal action, request company audits, and exercise appraisal rights when corporate actions are detrimental. However, the implementation of these rights remains suboptimal due to the dominance of majority shareholders under the “one share one vote” mechanism, limited access to strategic information, and the insufficient effectiveness of Independent Commissioners, supervisory committees, and the Sharia Supervisory Board. From a Sharia law perspective, GCG at BSI should not be understood merely as formal regulatory compliance, but as an integrated framework combining OJK regulations, corporate governance mechanisms, and Islamic values such as justice, trustworthiness, transparency, accountability, and protection of wealth. This study recommends strengthening regulatory enforcement, information disclosure, minority shareholder participation, and Sharia-based supervision to create a more equitable and accountable Islamic banking governance system.